Issues of international legal cooperation between the un and the Republic of Uzbekistan - Ergashev, Bahodir (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
New trends in the modern system of international relations, including the rapid development of globalization, the emergence and spread of new threats and dangers to humanity. In this sense, the issue of developing regional cooperation as a guarantee of the interests and security of the Central Asian countries is of great importance